1998
DOI: 10.1152/ajpendo.1998.274.5.e785
|View full text |Cite
|
Sign up to set email alerts
|

Training-induced alterations in fat and carbohydrate metabolism during exercise in elderly subjects

Abstract: Compared with young adults, fat oxidation is lower in elderly persons during endurance exercise performed at either the same absolute or relative intensity. We evaluated the effect of 16 wk of endurance training on fat and glucose metabolism during 60 min of moderate intensity exercise [50% of pretraining peak oxygen consumption (V˙o 2 peak)] in six elderly men and women (74 ± 2 yr). Training caused a 21% increase in meanV˙o 2 peak. The average rate of fat oxidation during exercise was greater after (221 ± 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
77
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(92 citation statements)
references
References 27 publications
14
77
0
1
Order By: Relevance
“…These enzymatic changes would have the net effect of decreasing fat oxidation relative to glucose oxidation and may partially explain the reduction in exercising fat oxidation observed in older individuals (Sial et al, 1996). Evidence to support this notion is provided by studies which show an increase in both the activity of enzymes involved in fat oxidation (Coggan et al, 1992a, b) and exercising fat oxidation (Sial et al 1998) following training. Furthermore, because endurance training is not associated with increased free fatty acid release in the elderly (Poehlman et al, 1994;Sial et al, 1998), changes in fat oxidation are likely due to intrinsic changes in the ability of skeletal muscle to oxidize fat during exercise and not to differences in free fatty acid availability.…”
Section: Oxidative Capacity Of Fat-free Massmentioning
confidence: 96%
See 1 more Smart Citation
“…These enzymatic changes would have the net effect of decreasing fat oxidation relative to glucose oxidation and may partially explain the reduction in exercising fat oxidation observed in older individuals (Sial et al, 1996). Evidence to support this notion is provided by studies which show an increase in both the activity of enzymes involved in fat oxidation (Coggan et al, 1992a, b) and exercising fat oxidation (Sial et al 1998) following training. Furthermore, because endurance training is not associated with increased free fatty acid release in the elderly (Poehlman et al, 1994;Sial et al, 1998), changes in fat oxidation are likely due to intrinsic changes in the ability of skeletal muscle to oxidize fat during exercise and not to differences in free fatty acid availability.…”
Section: Oxidative Capacity Of Fat-free Massmentioning
confidence: 96%
“…Evidence to support this notion is provided by studies which show an increase in both the activity of enzymes involved in fat oxidation (Coggan et al, 1992a, b) and exercising fat oxidation (Sial et al 1998) following training. Furthermore, because endurance training is not associated with increased free fatty acid release in the elderly (Poehlman et al, 1994;Sial et al, 1998), changes in fat oxidation are likely due to intrinsic changes in the ability of skeletal muscle to oxidize fat during exercise and not to differences in free fatty acid availability. Collectively, these results suggest that agerelated reductions in the capacity of skeletal muscle to oxidize fat may partially explain the lower exercising and postprandial fat oxidation in older individuals.…”
Section: Oxidative Capacity Of Fat-free Massmentioning
confidence: 97%
“…Part of the defect in fat oxidation might be explained by the altered body composition during aging, such as decreased muscle mass and increased fat mass (CallesEscandon et al, 1995). However, related studies showed differences of fat oxidation still exist when body composition was taken into account (Sial et al, 1996(Sial et al, , 1998. Also, it was proposed that insufficient physical exercise in the eldly might play a role in aging-associated fat metabolism disturbance (Seals et al, 1984;Cox et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…20 ± 23 Aerobic endurance exercise has traditionally been advocated as the most suitable exercise mode to prevent and treat DM. 24 ± 28 Exercise has been proven to be e ective in improving muscular, 21,26,27 adipose tissue 20,23,28 and whole body insulin sensitivity. 21,22,25 In one study, 10 subjects with Type 2 DM who had signi®cant insulin resistance and eight controls without insulin resistance were trained with 1 h of stair climbing for 6 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Results demonstrated that physical training signi®cantly improved insulin sensitivity in both the insulin resistance group and the control group by 43% compared to two drugs; metformin (16 ± 25%) or troglitazone (about 20%). The underlying mechanisms responsible for the improvements in muscle glucose metabolism are not fully understood but they seem to involve increases in the glucose transporter protein (GLUT-4), 28 increased blood¯ow, 29 body composition 20,23 and enzyme activities. 26,27 Although, there is enough evidence to conclude that exercise improves insulin sensitivity in the general population, there is a lack of information with respect to the e ects of exercise on insulin sensitivity in people with SCI.…”
Section: Introductionmentioning
confidence: 99%